Digitalisasi Perhitungan Pengujian Meter Air dan Timbangan Elektronik - Arviandi Subeny; Aditia Rafli I; M. Akmal, M; Fajar Sidiq; M. Zulfa Ibnu R (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The Bandung City Legal Metrology Unit is the Regional Technical Implementation Unit at the Bandung City Trade Office in carrying out official duties related to the application of measuring instruments, measures, weights and equipment (UTTP) including water meters and electronic scales. Before this application was made by the author, the Bandung City Legal Metrology Unit was required to test water meter meters at least four thousand a week, because the items tested were not a little difficult to test the measuring device because the calculation check was carried out manually. Therefore, to simplify and accelerate the task of testing water meter measuring instruments, an application was created that is able to calculate the testing of water meter measuring instruments and electronic scales to produce a decision on measuring instruments that are suitable for circulation in the community to test measuring instruments automatically. This test is carried out in the field so that the system created must also be mobile-based, the system is designed using a web kodular application. The creation of the application can help the tester in conducting tests faster and more accurately, and the testers can make an archive using the test counter application for measuring instruments and electronic scales.